Pengaruh Penerapan Media pembelajaran Quizwhizzer Terhadap Tingkat Pemahaman Siswa Kelas X Pada Mata Pelajaran Informatika SMA Kristen Tunas Gloria - Elisabet Beama; Yonly A. Benufinit; Diana Yanni Fallo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the effect of implementing Quizwhizzer learning media on the level of understanding of 10th-grade students in informatics at Tunas Gloria Christian High School. Quantitative research using experimental methods, a True Experimental design with a posttest-only control design was used to determine the effect of a specific treatment, namely the use of Quizwhizzer learning media, on students' level of understanding in informatics. The results of data analysis indicate that the application of Quizwhizzer learning media has an effect on students' level of understanding, with an average post-test result for the experimental group of 86.94 and an average post-test result for the control group of 73.82, with an average percentage of the research questionnaire of 85%. The results of the study concluded that there was a significant increase in students' level of understanding after students used Quizwhizzer learning media in informatics at Tunas Gloria Christian High School, Kupang.